Sustainability in multi‐tier supply chains: Understanding the double agency role of the first‐tier supplier - Wilhelm, Miriam M.; Blome, Constantin; Bhakoo, Vikram; Paulraj, Antony (Journal of Operations Management, 2016)
AbstractIn light of the growing complexity of globally dispersed, multi‐tier supply chains, the involvement of first‐tier suppliers has become instrumental in the quest for achieving sustainability compliance along the supply chain. We describe this new responsibility as the double agency role. We employ agency and institutional theory arguments to explore the conditions under which first‐tier suppliers will act as agents who fulfill the lead firm's sustainability requirements (i.e., the primary agency role) and implement these requirements in their suppliers' operations (i.e., the secondary agency role). The findings from three in‐depth case studies embedded in different institutional contexts highlight the importance for lead firms to incentivize each agency role separately and to reduce information asymmetries, particularly at the second‐tier level. In addition, our inductive analysis reveals several contingency factors that influence the coupling of the secondary agency role of the first‐tier supplier. These factors include resource availability at the first‐tier supplier's firm, the lead firm's focus on the triple‐bottom‐line dimension (i.e., environmental or social), the lead firm's use of power, and the lead firm's internal alignment of the sustainability and purchasing function. We integrate our findings in a conceptual framework that advances the research agenda on multi‐tier sustainable supply chains, and we subsequently outline the practical implications of assigning the double agency role to first tier suppliers.